A network meta-analysis to evaluate the efficacy of traditional Chinese medicine on intestinal flora in patients with gastrointestinal cancer - Feng, Niran; Wang, Shurui; Liu, Chengjiang; Xu, Zixin; Song, Zhijie; Li, Kunyang; Yu, Zhifeng (Frontiers in Genetics, 2022)
Background and Purpose Traditional Chinese medicine (TCM) can regulate intestinal flora so as to affect the occurrence, progression, and prognosis of gastrointestinal cancer. According to clinical studies, TCM oral administration , TCM external treatment, and TCM injections, can adjust intestinal flora disorders in patients with gastrointestinal cancer. This network meta-analysis aims to evaluate the effect of three treatments on the intestinal flora in gastrointestinal cancer patients . Methods This meta-analysis was registered in PROSPERO (CRD42022332553). Six electronic databases, namely CNKI, Wanfang,CSTJ, PubMed, Cochrane Library, and EMBASE, were searched from their inception to April 1, 2022. We identified randomized controlled trials (RCT) used to compare the efficacy of three TCM treatment methods—oral administration, external therapy and injections—on the intestinal flora in gastrointestinal cancer patients. The main outcome indicators were Bifidobacteria, Lactobacilli, Escherichia coli, and Enterococci. Stata(15.1) and the Cochrane risk of bias assessment tool were employed. Results We identified 20 eligible RCTs with a total of 1,774 patients. According to network meta-analysis results, TCM injection plus common treatment (CT) or oral administration of TCM plus CT was superior to CT alone for supporting Bifidobacterium. In supporting Lactobacillus, TCM injection plus CT demonstrated more obvious effect relative to oral administration of TCM plus CT; TCM injection plus CT was more effective than CT only; and oral administration of TCM plus CT was superior to CT only.The inhibitory effect of TCM injection plus CT on Escherichia coli was better compared with CT only. In terms of inhibiting Enterococci, oral administration of TCM plus CT was superior to CT only.The difference in efficacy among the above treatments was statistically significant. In the SUCRA probability ranking, TCM injection plus CT had the best ranking curve among the three treatments and was the most effective in supporting Bifidobacteria (Sucra = 90.08%) , Lactobacilli (Sucra= 96.4%), and regulating Escherichia coli (Sucra = 86.1%) and Enterococci (Sucra= 87.1% ). Conclusions TCM injections plus CT is the most effective therapy in balancing the intestinal flora of gastrointestinal cancer patients. However, the current results deserve further validation through high-quality research.